A decentralized congestion management using interior point method - Singh B.; Mahanty R.; Singh S.P. (My University, 2025)
This paper presents a framework to carry out an optimal power flow in a coordinated multi area decentralized system. An AC optimal power flow model is used for independent optimal dispatch of each area while the global economic optimal of whole electric energy system is achieved. This is achieved by means of the interior point optimization procedure. In this approach, each participant tries to maximize their own profit with the help of system information announced by the operator. The developed algorithm can be run in parallel either to carry out numerical simulations or in an actual multi area electric system. The simulation is conducted on a three area modified IEEE-30 bus system. The results show clearly the effectiveness of the suggested method. It is shown that the suggested decentralized approach can yield the same optimal dispatch solution as the centralized approach. © 2011 IEEE.